Genome Sequence of Bacillus subtilis subsp. spizizenii gtP20b, Isolated from the Indian Ocean - Fan, Longjiang (American Society for Microbiology (ASM), 2011)
Bacillus subtilis is an aerobic spore-forming Gram-positive bacterium that is a model organism and of great industrial significance as the source of diverse novel functional molecules. Here we present, to our knowledge, the first genome sequence of Bacillus subtilis strain gtP20b isolated from the marine environment. A subset of candidate genes and gene clusters were identified, which are potentially involved in production of diverse functional molecules, like novel ribosomal and nonribosomal antimicrobial peptides. The genome sequence described in this paper is due to its high strain specificity of great importance for basic as well as applied researches on marine organisms.